Massive Bioaccumulation and Self‐Assembly of Phenazine Compounds in Live Cells - Min, Kyoung Ah (Adv Sci (Weinh), 2015)
Clofazimine is an orally administered drug that massively bioaccumulates in macrophages, forming membrane‐bound intracellular structures possessing nanoscale supramolecular features. Here, a library of phenazine compounds derived from clofazimine is synthesized and tested for ability to accumulate and form ordered molecular aggregates inside cells. Regardless of chemical structure or physicochemical properties, bioaccumulation is consistently greater in macrophages than in epithelial cells. Microscopically, some self‐assembled structures exhibit a pronounced, diattenuation anisotropy signal, evident by the differential absorption of linearly polarized light, at the peak absorbance wavelength of the phenazine core. The measured anisotropy is well above the background anisotropy of endogenous cellular components, reflecting the self‐assembly of condensed, insoluble complexes of ordered phenazine molecules. Chemical variations introduced at the R‐imino position of the phenazine core lead to idiosyncratic effects on the compounds' bioaccumulation behavior as well as on the morphology and organization of the resulting intracellular structures. Beyond clofazimine, these results demonstrate how the self‐assembly of membrane permeant, orally bioavailable small molecule building blocks can endow cells with unnatural structural elements possessing chemical, physical, and functional characteristics unlike those of other natural cellular components.